REFORMING COMPULSORY HEALTH INSURANCE IN MARKET CONDITIONS - Kasimova D.A; Almardanov Sh.Q; Bozorov Z.K. (TADQIQOTLAR, 2026)
Abstract: The reform of compulsory health insurance systems within market- based frameworks represents one of the most significant challenges facing healthcare policy makers globally. This article examines the theoretical foundations, empirical evidence, and practical implementation strategies for reforming mandatory health insurance schemes while maintaining market efficiency, equity, and sustainability. Drawing upon extensive literature from health economics and policy research, we analyze the tensions between universal coverage mandates and market competition, explore various reform models from international experience, and identify key factors that determine reform success. The evidence suggests that effective reform requires careful balance between regulatory oversight and market mechanisms, with particular attention to risk selection, cost containment, and equitable access. We conclude with recommendations for policy makers seeking to navigate the complex terrain of health insurance reform in increasingly market-oriented healthcare systems.